Cocoa by-products extracts suppress viral replication and oxidative stress in chikungunya virus-infected cells - Sandra Johanna Morantes; Luisa Fernanda Daza; Alejandro Cáceres; Luis Felipe Gutiérrez; Martha Cecilia Rincón; Juan David Dereix; Félix Giovanni Delgado (PLoS ONE, 2026)
Context Studies have demonstrated a correlation between oxidative stress and Chikungunya virus (CHIKV) replication, underscoring the potential of these biochemical interactions for developing novel antiviral therapies. Since cocoa ( Theobroma cacao L. ) by-products have exhibited potent antiviral and antioxidant properties, they may represent a promising source for new therapeutic alternatives. Objective To assess the potential of cocoa pod husk (CPH) and cocoa bean shell (CBS) extracts to inhibit viral replication and oxidative stress in an in vitro model of CHIKV infection. Materials and methods The viability of Huh-7 cells in the presence of extracts (15.6 to 250 µg/mL), and CHIKV-infected cells treated with the extracts was evaluated using the resazurin reduction assay. Antiviral activity was determined by RT-qPCR and plaque assays, while reduction of oxidative stress in infected cells was measured using the dichloro-dihydro-fluorescein diacetate (DCFH-DA) assay at 12 and 24 hours post-infection (hpi). Results CPH and CBS extracts exhibited minimal cytotoxicity in Huh-7 cells. Remarkably, both extracts exhibited antiviral and antioxidant properties at concentrations above 62.5 µg/mL mainly at 12 hpi. This was evidenced by a significant reduction in viral RNA copies and infectious virus particles, as well as decreased levels of reactive oxygen species (ROS) in CHIKV-infected cells. Discussion and conclusion Cocoa extracts reduce the oxidative stress induced by CHIKV in Huh-7 cells while exhibiting antiviral properties, highlighting their potential to modulate both oxidative stress and viral replication. Further studies are recommended to elucidate the mechanisms by which these extracts work.